Risk of Knee Osteoarthritis With Obesity, Sarcopenic Obesity, and Sarcopenia. Issue 2 (4th January 2019) - Misra, Devyani; Fielding, Roger A.; Felson, David T.; Niu, Jingbo; Brown, Carrie; Nevitt, Michael; Lewis, Cora E.; Torner, James; Neogi, Tuhina; ,
Abstract : Objective: Obesity, defined by anthropometric measures, is a well‐known risk factor for knee osteoarthritis (OA), but there is a relative paucity of data regarding the association of body composition (fat and muscle mass) with risk of knee OA. We undertook this study to examine the longitudinal association of body composition categories based on fat and muscle mass with risk of incident knee OA. Methods: We included participants from the Multicenter Osteoarthritis Study, a longitudinal cohort of individuals with or at risk of knee OA. Based on body composition (i.e., fat and muscle mass) from whole‐body dual x‐ray absorptiometry, subjects were categorized as obese nonsarcopenic (obese), sarcopenic obese, sarcopenic nonobese (sarcopenic), or nonsarcopenic nonobese (the referent category). We examined the relationship of baseline body composition categories with the risk of incident radiographic OA at 60 months using binomial regression with robust variance estimation, adjusting for potential confounders. Results: Among 1, 653 subjects without radiographic knee OA at baseline, significantly increased risk of incident radiographic knee OA was found among obese women (relative risk [RR] 2.29 [95% confidence interval 95% CI 1.64–3.20]), obese men (RR 1.73 [95% CI 1.08–2.78]), and sarcopenic obese women (RR 2.09 [95% CI 1.17–3.73]), but not among sarcopenic obese men (RR 1.74 [95% CI 0.68–4.46]). Sarcopenia was not associated with risk of knee OA (for women, RR 0.96 [95% CI 0.62–1.49]; for men, RR 0.66 [95% CI 0.34–1.30]). Conclusion: In this large longitudinal cohort, we found body composition–based obesity and sarcopenic obesity, but not sarcopenia, to be associated with risk of knee OA. Weight loss strategies for knee OA should focus on obesity and sarcopenic obesity.